Beyond daily totals: meal-level digestible indispensable amino acid score reveals how food groups shape protein quality in vegan diets - Soh, Bi Xue Patricia; Vignes, Matthieu; Smith, Nick W.; von Hurst, Pamela R.; McNabb, Warren C. (Frontiers in Nutrition, 2026)
IntroductionVegan diets rely solely on plant-based proteins, which often supply fewer digestible indispensable amino acids (IAAs) than omnivorous diets. Low protein quality can leave IAAs undersupplied even if the protein intake meets the recommended intakes. Mixtures of plant-based foods in meals can complement limiting IAAs and improve the synchronized delivery of all IAAs for optimal metabolic function. Assessing how food group compositions differ among meals of varied protein quality is essential to determine the ideal proportions of plant-based foods to improve the Digestible Indispensable Amino Acid Score (DIAAS) of vegan meals.MethodsThe DIAAS was calculated for each meal found in the 4-day food diaries of 193 New Zealand vegans. Principal component analysis and k-means clustering were applied to identify food groups associated with meals of varying DIAAS, and meal level clusters were compared to participants’ daily protein intake.ResultsEight distinct meal clusters emerged. Lower-DIAAS meals were characterized by higher quantities of fruit, grain foods, potatoes, and sugary condiments with significantly lower (p < 0.001) weight share of legumes than higher-DIAAS meals, which had a ~ 2:1 legume: grain profile. IAA contribution differed across plant-based food groups as grains, nuts, and seeds supplied more sulfur-amino acids while legumes and extruded plant protein isolates (such as protein powders) supplied more lysine. Notably, lower protein quality meals appeared most often in daily patterns with lower total protein and IAA intake, but also occurred when daily protein was high, underscoring that day-level protein adequacy can mask meal-level deficits.DiscussionDeliberate meal-level complementation of plant-based foods is necessary to ensure protein quality in vegan dietary patterns.